Dynamic allocation of spectrum resources in heterogeneous networks under interference constraints. (1st January 2012) - Hamouda, Soumaya; Hamdaoui, Bechir
The next generation of radio wireless networks is expected to support spectrum decision operations that will allow a cognitive radio terminal to share the frequency bandwidth with primary users (PUs) without impairing their QoS requirements. This can indeed enhance the utilisation of the limited spectrum resources, and help meet the growing bandwidth demand. In this paper, we propose a new, cross-layer algorithm that allows a cognitive terminal (CT) to share and access to either HSDPA or WiMAX licensed spectrum while giving priority to the PUs. This algorithm not only considers the interference caused by the CT, but also enhances the achievable throughput of this CT. Simulation results show the effectiveness of our spectrum access scheme. Under our proposed scheme, the achievable data rate of the cognitive radio terminal is increased by 30% when compared with that obtained under common access schemes